2019
DOI: 10.1021/acs.jpclett.9b02868
|View full text |Cite
|
Sign up to set email alerts
|

An Allosteric Pathway in Copper, Zinc Superoxide Dismutase Unravels the Molecular Mechanism of the G93A Amyotrophic Lateral Sclerosis-Linked Mutation

Abstract: Several different mutations of the protein copper, zinc superoxide dismutase (SOD1) produce the neurodegenerative disorder amyotrophic lateral sclerosis (ALS). The molecular mechanism by which the diverse mutations converge to a similar pathology is currently unknown. The electrostatic loop (EL) of SOD1 is known to be affected in all of the studied ALS-linked mutations of SOD1. In this work, we employ a multiscale simulation approach to show that this perturbation corresponds to an increased probability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Most of these issues are inherent to the process of coarse-graining, but some of these problems can be alleviated at least to some extent. For instance, protein flexibility can be greatly improved by the combination of Martini and Gō-like models 85,86 . Hydration of pockets can be modeled by the usage of smaller water beads, as it was already applied here in the A 2A R and β2AR case (see Supplementary Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these issues are inherent to the process of coarse-graining, but some of these problems can be alleviated at least to some extent. For instance, protein flexibility can be greatly improved by the combination of Martini and Gō-like models 85,86 . Hydration of pockets can be modeled by the usage of smaller water beads, as it was already applied here in the A 2A R and β2AR case (see Supplementary Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has suggested that Cu dyshomeostasis contributes to the onset of the most common neurodegenerative disorders besides AD, including Parkinson’s disease, prion-mediated encephalopathies, Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS) [ 78 , 79 , 80 , 81 ]. Hence, circumstances leading to a higher or lower copper concentration can be hazardous to health, such as Menkes diseases, a genetic disorder of Cu deficiency [ 82 , 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on contacts defined by an overlap and contacts of structural units-criterion evaluated only for the residues resolved in the crystal structure, Lennard-Jones interactions were added up to a cutoff distance of 1.1 nm (Thallmair et al, 2019). The dissociation energy of the Lennard-Jones potential was set to ε = 12.0 kJ/mol (Souza et al, 2019). In total, 541 Gō-like bonds were added for tubbyCT.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%